2004
DOI: 10.1023/b:pham.0000036909.41843.18
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Chemical Structure and the Surface Properties of Polymeric Biomaterials on Their Biocompatibility

Abstract: Polymeric biomaterials have extensively been used in medicinal applications. However, factors that determine their biocompatibility are still not very clear. This article reviews various effects of the chemical structure and the surface properties of polymeric biomaterials on their biocompatibility, including protein adsorption, cell adhesion, cytotoxicity, blood compatibility, and tissue compatibility. Understanding these aspects of biocompatibility is important to the improvement of the biocompatibility of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
253
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(263 citation statements)
references
References 88 publications
9
253
0
1
Order By: Relevance
“…The surface properties of an implanted biomaterial are of the utmost importance for its biocompatibility. As for a biomaterial surface, the cell-material interaction is strongly influenced by not only surface topography but also by surface chemistry (physicochemical property) including surface wettability (surface energy) and surface charge [1][2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…The surface properties of an implanted biomaterial are of the utmost importance for its biocompatibility. As for a biomaterial surface, the cell-material interaction is strongly influenced by not only surface topography but also by surface chemistry (physicochemical property) including surface wettability (surface energy) and surface charge [1][2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…A high water level on the surface of the biomaterial provides a low interfacial tension with blood, thus reducing fibrinogen adsorption, cell adhesion and clot formation, (Abraham, 2002;Faibish, 2002;Van Krevelen, 1990;Wang, 2004). The results are presented in Fig 2. It is observed that the water uptake is given by the PEA-PU sample (reference polyurethane sample without hydroxypropylcellulose, PEA/MDI/EG, M n =109.613, M w /M n =1.3), PEA-HPC and PTHF-HPC samples (151 %, 140 % and 167 %, respectively ) and in a less extent by the PPG-HPC (92 %) due to its less polar soft segment having the lateral -CH 3 substituent which confer a different geometry to the polyurethane internal microporous structure, unfavorable for water uptake.…”
Section: Water Sorptionmentioning
confidence: 99%
“…In case of the preferentially fibrinogen adsorption (important protein in endogenous haemostasis), platelet adhesion is increased followed by thrombus activation and clot formation. In case of albumin absorbtion platelet adhesion is diminished which confer to the surface a thromboresistant character, (Bajpai, 2005;Wang et al, 2004). Fig.…”
Section: Platelet Adhesionmentioning
confidence: 99%
“…These methods do not require hazardous chemicals, yet still have the capability to modify the surface while imparting less degradation and roughness compared to wet chemical surface modification techniques [26]. In addition, the film deposited on the polymer surface can be manipulated by changing the deposition rate, energy range and surface topography [97]. Plasma pre-treatment has also been used prior to attaching collagen to a polymer nanofiber mesh, a method that showed increased cell attachment, spreading and viability [98].…”
Section: Attachment Of Pharmaceuticals Biopharmaceuticals or Biomolementioning
confidence: 99%